Structural Analysis of Epinephrine by Combination of Density Functional Theory and Hartree-Fock Methods - Omar, Rebaz Anwar; Ahmed, Lana Omer; Hama, Jawameer R.; Koparir, Pelin (TUBITAK, 2022)
In this study, we built a model to predict the structure and chemical properties of epinephrine using Density Functional Theory (DFT) and Hartree-Fock (HF) methods, as the methods currently playing a significant role in computational quantum theories. Six basis sets of DFT and HF methods were used to calculate bandgap energies to find the minimum energy bandgap. The basis set 6-311++G was further used to characterize the most stable molecular geometry of epinephrine, as well as the molecular characteristics. Then, the basis set B3LYP/6-31G(d,p) applied on epinephrine to investigate the energy of the highest occupied molecular orbital (EHOMO), the energy of the lowest unoccupied molecular orbital (ELUMO), energy gap (?E = ELUMO-EHOMO) and the dipole moment (?). The fraction of transferred electrons (?N) was also calculated, which determined the interaction between the iron surface and the epinephrine compound. Corrosion inhibitor behavior can therefore be predicted from the calculated data without an experimental study. The findings of the calculations show good relation between organic-based corrosion inhibitors and quantum chemical parameters process. The parametrization and stimulation optimized in this study can be used as a model to predict the chemical structure and activity of any compound with the known chemical formula. © 2022, TUBITAK. All rights reserved.
Yoğunluk Fonksiyonel Teorisi ve Hartree-Fock Yöntemlerinin Kombinasyonu ile Epinefrinin Yapısal Analizi
Keywords: Adrenaline; structure stimulation; anti-corrosion activity; charge distribution; vibration frequency